Or just feel free to tell me how to do them , by using an example as well pleas!
If g(3) = 12, then g(x) = 2x +
If f(-3) = -8, then f(x)= 3x +
If f(x) = 25 - 2x, then f(5) =
If f(3) = 20, then f(x) = 5x +
If g(4) = 16, g(5) = 18, g(6) = 20, then g(3) =
If f(2)= 20, f(3) = 25, f(4) = 30, f(5) = 35, then f(7) =
f(7) = 18, then f(x) = 2x +
If f(x) = 3x - 12, then f(4) =
If g(t) = 4 - 3t, then g(-2)=

Respuesta :

1. g(x)=2x+6
2.f(x)=3x+1

basically f(x) means that x is any number. So f(3) means that that number is 3. Now when you do f(x)=2x that's just saying f(3)=2(3), or 2*3=6. Everytime you evaluate f(x) for any number of x, you take every x on the right side of the equation and input it with that number. 2x does not become 23, but 2*x.

Now you know that f(-3)=-8 and the equation has f(x)=3x. Now every linear function has a constant. Sometimes that constant is zero which gives the appearance there is no constant. Now your job is to figure out what the constant is. So f(-3) and f(x)=3x means that f(-3)=3*(-3)+constant. Now 3*-3=-9, and we know f(-3)=-8, so that means your function is 3x+1.